«Celestina» comentada, ed. Luoise Forthergill-Payne, Enrique Fernández Rivera y Peter Forthergill-Payne. Salamanca, Ediciones de la Universidad de Salamanca, 2002 - López-Ríos, Santiago (Celestinesca, 2021)
N/A